2014
DOI: 10.1021/jp408584v
|View full text |Cite
|
Sign up to set email alerts
|

Chromophore Dynamics in the PYP Photocycle from Femtosecond Stimulated Raman Spectroscopy

Abstract: Femtosecond stimulated Raman spectroscopy (FSRS) is used to examine the structural dynamics of the para-hydroxycinnamic acid (HCA) chromophore during the first 300 ps of the photoactive yellow protein (PYP) photocycle, as the system transitions from its vertically excited state to the early ground state cis intermediate, I0. A downshift in both the C7═C8 and C1═O stretches upon photoexcitation reveals that the chromophore has shifted to an increasingly quinonic form in the excited state, indicating a charge sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 46 publications
(119 reference statements)
3
39
0
Order By: Relevance
“…Furthermore, the C1=O1 carbonyl out-of-plane vibration downshifts from 665 to 640 cm -1 concurrent with excited state decay which was interpreted as resulting from motion along the photoisomerisation coordinate [31]. The correspondence between X-ray structural and Raman structural measurements of Franck-Condon motions in PYP also highlights that selection rules must be considered for each ultrafast observation.…”
Section: Primary Photochemical Reactions and Coherence Of Pypmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, the C1=O1 carbonyl out-of-plane vibration downshifts from 665 to 640 cm -1 concurrent with excited state decay which was interpreted as resulting from motion along the photoisomerisation coordinate [31]. The correspondence between X-ray structural and Raman structural measurements of Franck-Condon motions in PYP also highlights that selection rules must be considered for each ultrafast observation.…”
Section: Primary Photochemical Reactions and Coherence Of Pypmentioning
confidence: 89%
“…Creelman et al [31] observed using femtosecond stimulated Raman spectroscopy a FranckCondon intermediate already at ~100 fs, distinct from the major S1 decay process with a ~450 fs time constant. The FC state already showed gained intensity of a 958 cm -1 Hydrogen-outof-plane (HOOP) mode, indicative of chromophore distortion at the ethylenic C2=C3 [31].…”
Section: Primary Photochemical Reactions and Coherence Of Pypmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature evidence suggests (Nakamura et al ., 2007; Creelman et al ., 2014) that the pCA isomerization takes place on an ultrafast, sub-ps time scale. The ultrafast, fs X-ray pulses available at the XFEL were exploited to structurally characterize this transition (Pande et al ., 2016).…”
Section: Xfel Example: Early Events In the Photoactive Yellow Protmentioning
confidence: 99%
“…The FSRS technology has been successfully applied to a number of important photosensitive molecular systems including rhodopsin [27], bacteriorhodopsin [28], phytochrome [29], organic dyes in solar cells [30], Fe(II) spin crossover in solution [31], fluorescent proteins [7,32,33], and calcium-ion-sensing protein biosensors [34][35][36]. The main goal of this work is to construct a versatile, tunable FSRS setup that extends the wavelength detection window to the UV regime with desired resonance Raman enhancement.…”
Section: Resultsmentioning
confidence: 99%